Faktor-Faktor Yang Mempengaruhi Tingkat Kepuasan Pasien Di Poli Gigi Riksa Diri Kabupaten Bandung - Ardiani, Annisa Aulia; Heriyanto, Yonan; Nurnaningsih, Hera; Chaerudin, Denden Ridwan (Poltekkes Kemenkes Bandung, 2023)
In health services, patients are consumers of health services, it is very important to know patient satisfaction because patient satisfaction is part of service quality. This study aims to determine the factors influencing of patient satisfaction levels at the Poli Gigi Riksa Diri Kabupaten Bandung. This research is a descriptive research. The study was conducted in March-April 2022. This study used primary data obtained directly from respondents with a list of questionnaires. The sampling technique was carried out using purposive sampling technique with a sample of 71 respondents. Data processing is performed quantitatively with the criteria of value weighting using a Likert scale and data analysis using percentage analysis of all answers filled out by respondents. The results of study on factors influencing of patient satisfaction levels at the Poli Gigi Riksa Diri Kabupaten Bandung described that patient satisfaction with responsiveness with a percentage of score 93%, assurance with a percentage number of score 95.8%, reliability with a percentage of 93%, empathy with a number of score 94.4%, tangibles with a percentage of 91.5% was included that respondents are satisfied with the services provided.